Emergence of MicroRNAs as Key Players in Cancer Cell Metabolism. (1st September 2019) - Subramaniam, Sugarniya; Jeet, Varinder; Clements, Judith A; Gunter, Jennifer H; Batra, Jyotsna
Abstract: BACKGROUND: Metabolic reprogramming is a hallmark of cancer. MicroRNAs (miRNAs) have been found to regulate cancer metabolism by regulating genes involved in metabolic pathways. Understanding this layer of complexity could lead to the development of novel therapeutic approaches. CONTENT: miRNAs are noncoding RNAs that have been implicated as master regulators of gene expression. Studies have revealed the role of miRNAs in the metabolic reprogramming of tumor cells, with several miRNAs both positively and negatively regulating multiple metabolic genes. The tricarboxylic acid (TCA) cycle, aerobic glycolysis, de novo fatty acid synthesis, and altered autophagy allow tumor cells to survive under adverse conditions. In addition, major signaling molecules, hypoxia-inducible factor, phosphatidylinositol-3 kinase/protein kinase B/mammalian target of rapamycin/phosphatase and tensin homolog, and insulin signaling pathways facilitate metabolic adaptation in tumor cells and are all regulated by miRNAs. Accumulating evidence suggests that miRNA mimics or inhibitors could be used to modulate the activity of miRNAs that drive tumor progression via altering their metabolism. Currently, several clinical trials investigating the role of miRNA-based therapy for cancer have been launched that may lead to novel therapeutic interventions in the future. SUMMARY: In this review, we summarize cancer-related metabolic pathways, including glycolysis, TCA cycle, pentose phosphate pathway, fatty acid metabolism, amino acid metabolism, and other metabolism-related oncogenic signaling pathways, and their regulation by miRNAs that are known to lead to tumorigenesis. Further, we discuss the current state of miRNA therapeutics in the clinic and their future potential.